DAERAH SALJU YANG “DINGIN” Tinjauan terhadap Novel Daerah Salju Karya Kawabata Yasunari - Fajria Noviana (IZUMI, 2014)
Expressive approach on this novel was conducted to proof scholars’ opinions about the themes that Kawabata often used in his works, which affected by his unpleasant childhood. Those themes are loneliness, emptiness, broken heart, sexuality, and others in common. Comparative study was also conducted but to find out how this novel affected by other literary works and  Japanese traditions, and vice versa.